2018
DOI: 10.1139/cjpp-2018-0112
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and homocysteine-related compounds: an overview of the roles in the pathology of the cardiovascular and nervous systems

Abstract: Homocysteine, an amino acid containing a sulfhydryl group, is an intermediate product during metabolism of the amino acids methionine and cysteine. Hyperhomocysteinemia is used as a predictive risk factor for cardiovascular disorders, the stroke progression, screening for inborn errors of methionine metabolism, and as a supplementary test for vitamin B deficiency. Two organic systems in which homocysteine has the most harmful effects are the cardiovascular and nervous system. The adverse effects of homocystein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 164 publications
2
63
0
1
Order By: Relevance
“…Recently, it has been confirmed that hyperhomocysteinemia is an independent risk factor for CVD [8]. Hyperhomocysteinemia may contribute to atherosclerosis by the action of several different mechanisms, such as overactivation of N-methyl-d-aspartate receptors, activation of Toll-like receptor 4, disturbance in Ca 2 + handling, increased activity of nicotinamide adenine dinucleotide phosphate-oxidase and subsequent increase of production of reactive oxygen species, increased activity of nitric oxide synthase and nitric oxide synthase uncoupling and consequent impairment in nitric oxide and reactive oxygen species synthesis, as well as increased expression of several proinflammatory cytokines, including IL-1β, IL-6, TNF-α, MCP-1, and intracellular adhesion molecule-1 [25]. Meanwhile, a recent meta-analysis study showed that acute coronary syndrome patients with the highest Hcy level had an increased risk of major adverse cardiovascular events (RR = 2.01; 95 % CI: 1.53-2.64) and all-cause mortality (RR = 2.05; 95 % CI: 1.50-2.79) after controlling confounding factors [26].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been confirmed that hyperhomocysteinemia is an independent risk factor for CVD [8]. Hyperhomocysteinemia may contribute to atherosclerosis by the action of several different mechanisms, such as overactivation of N-methyl-d-aspartate receptors, activation of Toll-like receptor 4, disturbance in Ca 2 + handling, increased activity of nicotinamide adenine dinucleotide phosphate-oxidase and subsequent increase of production of reactive oxygen species, increased activity of nitric oxide synthase and nitric oxide synthase uncoupling and consequent impairment in nitric oxide and reactive oxygen species synthesis, as well as increased expression of several proinflammatory cytokines, including IL-1β, IL-6, TNF-α, MCP-1, and intracellular adhesion molecule-1 [25]. Meanwhile, a recent meta-analysis study showed that acute coronary syndrome patients with the highest Hcy level had an increased risk of major adverse cardiovascular events (RR = 2.01; 95 % CI: 1.53-2.64) and all-cause mortality (RR = 2.05; 95 % CI: 1.50-2.79) after controlling confounding factors [26].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, methylmercury may act in response with GSH to form a GSH S-conjugate (CH 3 Hg-S-G), which can then be catabolized to CH 3 Hg-S-Cys by the sequential activities of γ-glutamyltransferase and cysteinylglycinase/aminopeptidase M located in epithelial cell [71,73]. Because of the attendance of a large hydrophobic side group and structural connection to methionine, CH 3 Hg-S-Cys may be transported addicted to cells via the amino acid transporter, system L [73]. This transporter has a similarity with large hydrophobic amino acids, as well as L-methionine [73].…”
Section: Mercury (Hg)mentioning
confidence: 99%
“…Homocysteine (Hc) is a sulpho-amino acid formed by interconversion of methionine and cysteine (Cys). Most of the Hc in the blood is in a protein-bound state, although some are oxidized to Hc and homocysteic acid (HCA) or forms mixed heterodimers with Cys [1][2][3]. It is present in three different forms: around 1% circulates as free thiol, 70-80% remains disulfide-bound to plasma proteins, mainly albumin, and 20-30% combines with itself to form the dimer Hc or with other thiols [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Given the fact that NMDAR is Ca2+ channel, it was of great interest to estimate its presence and function in the heart, an organ whose function is strictly dependent on equilibrium in intracellular Ca2+ homeostasis (10)(11)(12). The link between NMDAR and cardiovascular pathology came into focus due to detrimental effects of homocysteine (Hcy) on the cardiovascular system and its underlying mechanisms (13). Actually, it is proposed that Hcy induces overactivation, as well as overexpression, of NMDARs in cardiovascular tissues during hyperhomocysteinemia (HHcy).…”
Section: Introductionmentioning
confidence: 99%